The Desert in Pre-Islamic Poetry: A Perspective on Content and Art - Waked, Ismaael AbdAlrhman (Journal of Arabic Language Sciences and Literature, 2025)
This study aims to examine the desert environment in pre-Islamic poetry by analyzing its images and meanings in the works of poets from that era, dividing it into a living environment (living creatures such as the she-camel, sandgrouse, and water) and a silent environment (inanimate landmarks such as the night, mountains, and sand). The main objective is to uncover the pre-Islamic poet’s perception of the desert environment and how he employed its elements to express his psychological states, social values, and intended messages.The study adopts the analytical method by selecting pre-Islamic poetic samples and conducting semantic and symbolic analysis, supported by previous studies and heritage sources, while linking poetic imagery to the characteristics and components of the desert environment.The findings reveal that the desert environment formed a rich source for pre-Islamic poetry, and that poets consciously classified its elements into living and silent. Living elements were often used as means to overcome the challenges of the silent environment. The study also shows that the poet’s depiction of the desert was not mere natural description but a tool to demonstrate courage, highlight social values, and convey human emotions. It further indicates an interdependent relationship between the two environments, with the living often serving as the means of survival in the silent.The study concludes that the desert’s presence in pre-Islamic poetry reflects the deep connection between the poet and his surroundings, and his ability to transform it from a desolate space into a symbolic realm rich in meaning. It recommends expanding research into the desert’s presence in later literary periods, comparing it with its depiction in pre-Islamic poetry, focusing on the evolution of meanings and imagery, and emphasizing the study of human–environment relations in classical Arabic literature as a key to understanding its aesthetic and intellectual structure.
Keywords: desert; pre-Islamic poetry; living environment; silent environment; desert connotations